Tissue biomarker panel as a surrogate marker for squamous subtype of pancreatic cancer. Issue 8 (August 2020) - Sahni, Sumit; Moon, Elizabeth A.; Howell, Viive M.; Mehta, Shreya; Pavlakis, Nick; Chan, David; Ahadi, Mahsa S.; Gill, Anthony J.; Samra, Jaswinder; Mittal, Anubhav
Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) has been recently classified into four subtypes based on the gene expression levels, with squamous subtype having worst prognostic outcomes. However, gene expression analysis for each individual patient is not clinically feasible due to very high associated cost. We previously reported that levels of three biomarkers (S100A4, Ca-125 and Mesothelin) can be used to classify PDAC patients based on their survival outcomes. This project aimed to determine if this novel biomarker panel can be used as a surrogate to identify squamous PDAC subtype. Methods: Using the Nanostring gene expression platform, tumor tissue from 24 PDAC patients were analysed for our novel biomarkers and markers associated with four PDAC subtypes. Results: Gene expression of our biomarker panel (S100A4, Ca-125 and Mesothelin) closely clustered together with markers for squamous PDAC subtype. Conclusion: These results highlight the potential of our biomarkers to be utilized for identification of squamous PDAC subtype.